Phase-change material-integrated thermoelectric radiant panel: Experimental performance analysis and system design. (25th July 2021) - Kang, Yong-Kwon; Lim, Hansol; Cheon, Seong-Yong; Jeong, Jae-Weon
Highlights: A phase-change material (PCM)-integrated thermoelectric radiant cooling panel has been investigated. Empirical models predicting panel performances for various operating conditions were proposed. The optimum thickness of the PCM layer was also determined via a multi-objective optimization approach. Abstract: The objective of this research was to experimentally analyze the cooling performance of a phase-change material-integrated thermoelectric radiant cooling panel (PCM–TERCP) under active and passive cooling operation modes. Empirical models were derived for the PCM–TERCP to provide the available cooling capacity, duration time, and electric power consumption of the panel for the melting period (passive cooling mode) and solidifying period (active cooling mode) under a given operating condition. In the experiments, the durations of both the active and passive cooling were extended by up to 4 h when the thickness of the PCM layer increased from 5 mm to 15 mm. The mean cooling capacities of the proposed panel under the active cooling and passive cooling modes were approximately 58 W/m 2 and 54 W/m 2, respectively, when the mean radiant temperature (MRT) was 26 °C. Both cooling capacities decreased under lower MRT conditions. Empirical correlations for the cooling duration, cooling capacity, and electric power consumption of the proposed panel were used as objective functions to determine the optimum PCM layer thickness. The optimum PCM thickness of the proposed panel was determined to be 6–8 mm when providing a higher weight to minimizing the electric power consumption than to maximizing the cooling capacity.